Antidiabetic activity of Cassia sophera in STZ induced diabetic rats and its effect on insulin secretion from isolated pancreatic islets - Poonam Sharma,; Rambir Singh,; Priyanka Bhardwaj, (International Journal of Phytomedicine, 2013)
The aim of the study was to evaluate the antidiabetic effect of Cassia sophera seed extracts in streptozotocin (STZ) induced diabetic Wistar rats. Aqueous extract of Cassia sophera (AECS) showed maximum fall (60.88%, p<0.01) in 0 to 1 h fasting blood glucose during glucose tolerance test in normal healthy rats. Since AECS exhibited potential hypoglycemic activity, it was further studied for antidiabetic effect in STZ induced diabetic rats. The oral effective dose (ED50) of AECS was 200 mg/kg body weight which produced a fall of (70.50%, p<0.01) in diabetic rats. Treatment with AECS significantly reduced the elevated glycosylated haemoglobin (45.67%, p<0.05) and increased insulin level (40.6%, p<0.01). Total cholesterol (19.05%) low density lipoprotein (21.41%), triglyceride (57.87%) levels and very high density lipoprotein (57.85%) were significantly decreased (p<0.05) whereas, high density lipoprotein was significantly increased (38.58%, p>0.05) in diabetic rats. Since AECS treatment resulted in significant increase in serum insulin, its effect on insulin secretion in isolated pancreatic islets was also studied. AECS stimulated insulin secretion from the isolated islets at 3.3 and 16.7mM glucose. The effect of AECS was dose dependent. AECS induced enhancement in insulin secretion was not diminished by nicorandil, suggesting that AECS induced insulin secretion was independent of K-ATP channels of β cells.